Drugs acting at 5‐HT4, D2, motilin, and ghrelin receptors differ markedly in how they affect neuromuscular functions in human isolated stomach. Issue 6 (20th April 2014) - Broad, J.; Góralczyk, A.; Mannur, K.; Dukes, G. E.; Sanger, G. J.
Abstract Background Progress in identifying safer, effective drugs to increase gastric emptying is impeded by failed clinical trials. One potential reason for failure is lack of translation from animal models to the human condition. To make progress, the actions of existing drugs and new therapeutic candidates need to be understood in human isolated stomach. Methods Neuromuscular activities were evoked in human gastric antrum circular muscle by electrical field stimulation (EFS), defined phenotypically using pharmacological tools. Key Results EFS evoked cholinergically mediated contractions, attenuated by simultaneous nitrergic activation. The 5‐HT4 receptor agonist/D2 antagonist metoclopramide and the selective 5‐HT4 agonist prucalopride, facilitated contractions in the absence (respectively, Emax 95 ± 29% and 42 ± 9%, n = 3–6 each concentration) and presence (139 ± 38%, 55 ± 13%, n = 3–5) of the NO synthase inhibitor L‐NAME, without affecting submaximal contractions to carbachol; the 5‐HT4 antagonist SB204070 prevented facilitation by metoclopramide 100 μM (respectively, −5 (range −26 to 34) and 167 (12–1327)% in presence and absence; n = 5–6). The selective motilin receptor agonist camicinal provided considerably greater facilitation (478 (12–2080)% at 30 μM, n = 8). Domperidone (0.001–100 μM; n = 3–6) and acylated or des‐acylated ghrelin (1–300 nM; n = 2–4) had no consistent activity, even with protease inhibitors. Conclusions & Inferences 5‐HT4 receptor agonists show different efficacies. Motilin receptor activation has greater potential to increase gastric emptying, whereas ghrelin and D2 receptor antagonism have no direct activity. Drugs stimulating human gastric motility directly can act regardless of disease mechanisms, whereas drugs without direct activity but an ability to block nausea/vomiting may be effective only if these symptoms exist.